Microfluidics approaches for label-free isolation of extracellular vesicles from blood - Leong, Sheng Yuan (Nanyang Technological University, 2023)
Extracellular vesicles (EVs) are small membrane-bound particles secreted by cells and found in different biofluids (blood, urine, etc). They are key mediators of intercellular communication and are widely associated with many diseases including cancers and cardiovascular diseases. While EVs are emerging diagnostic biomarkers due to their disease-specific cargoes (e.g. proteins, DNAs RNAs), clinical adoption of EV-based testing remains challenging due to the inefficient and laborious EV isolation methods, thus advocating an unmet need to develop novel EV sample preparation tools. In this PhD thesis, we first present a comprehensive literature review to compare EV isolation using conventional methods and microfluidic approaches (Chapter 2), Next, we report a novel microfluidic platform technology (ExoDFF) for direct and label-free EV isolation from blood (Chapter 3). Based on the principle of non-equilibrium Dean vortices induced particle migration in a spiral microchannel, separation resolution was increased by 10-fold as compared to conventional inertial microfluidics. This enables simultaneous fractionation of small EVs (< 1 μm, sEV) and large EVs (1 ~ 2 μm, lEV) with 3-fold higher recovery than the current gold standard of ultracentrifugation (UC). The ExoDFF device was clinically validated in healthy and type 2 diabetes mellitus (T2DM) subjects where we identified “high-risk” T2DM individuals with abnormally high platelet- (CD41a+) and leukocyte-derived (CD45+) lEV in their blood samples, and their EVs were observed to induce significantly higher vascular inflammation (ICAM-1) (P < 0.05) in the in-vitro endothelial cell assay. These results indicate that ExoDFF is a gentle method for single-step EV isolation from blood for downstream functional assays. To further increase the sample throughput for EV-based diagnostics, we designed a short arcuated channel (ExoArc) based on similar separation principle to achieve an unprecedented throughput of 1 mL whole blood in 10 min (Chapter 4). The eluted cell-free and EV-rich plasma can be directly coupled with commercial size exclusion chromatography (SEC) to deplete the plasma proteins. Performance of EV separation was quantified using nanoparticle tracking analysis (NTA) for EV size/concentration, Western blots for EV-associated protein markers and transmission electron microscopy (TEM) for EV morphology. In a pilot clinical study of healthy subjects (n = 19) and non-small-cell lung cancer (NSCLC) patients (n = 20), plasma samples were processed using ExoArc for microRNA analysis (NanoString). A panel of 8 miRNAs were identified to classify both cohorts with 80% sensitivity and 89% specificity, thus indicating potential diagnostic value of circulating miRNAs in NSCLC patients. As a proof-of-concept for rapid EV isolation from cell culture media, a 3D-printed portable peristaltic pump system was built for automated in-line ExoArc processing to monitor EV production in healthy and inflamed human aortic endothelial cell (HAoEC) culture. While ExoDFF and ExoArc enable efficient EV isolation from blood directly, depletion of plasma proteins from eluted EVs is necessary for proteomics and biomarker discovery studies. In the final thesis chapter, we developed a novel rapid (~ 20 min) prototyping approach using commercial UV glue (NOA81) to fabricate a low-cost microfluidic SEC platform (μSEC) for EV separation from plasma proteins. The device can handle high pressure flow (up to 6 bar) and the built-in tubing connectors allow flexible interfacing with upstream sample preparation tools (e.g. ExoDFF/ExoArc) or downstream EV detectors. An on-chip sample injector with minimal dead volume was also added to the μSEC device to enable rapid (~ 1.5 s) and tiny volume (~ 600 nL) sample plug injection. Device validation using NTA and bicinchoninic acid assay (BCA) showed consistent performance between μSEC and commercial SEC in purifying EVs from undiluted human plasma. In summary, this thesis reports the technological advancement of several label-free size-based microfluidic EV preparation tools based on the principles of inertial microfluidics and SEC. These devices enable direct and automated EV isolation from blood which cannot be achieved using conventional centrifugation-based methods. Device validation using clinical samples also suggests new EV’s association with T2DM and NSCLC which can be further explored as potential biomarker. We envision these microfluidic modules can be readily integrated to offer a “sample-in-answer-out” solution for EV-based clinical diagnostics.